Financing social enterprises and the demand for social investment1. (13th January 2019) - Lyon, Fergus; Owen, Robyn
Abstract: Social investors are supplying increasing amounts of finance to enterprises combining social and commercial objectives although these social enterprises are still more likely to seek bank finance, suggesting that social investors should focus on market gaps which are more likely to occur for smaller, younger social enterprises that lack track record and collateral. Social enterprises offer innovative ways of combining social and commercial objectives and are only slightly less likely to seek repayable finance than other small and medium‐sized enterprises (SMEs), with younger social enterprises being more growth oriented and also more discouraged from borrowing. Where social enterprise borrowing takes place, it is almost three times more likely to be from commercial banks, rather than specialist social investment lenders that are more likely to invest without requiring collateral. Social investment lenders should therefore focus their offer on finance gaps left by banks, notably in earlier stage social enterprise development, rather than compete for existing commercial bank market share.